Antioxidant and Anti-Inflammatory Properties of Hydroxyl Safflower Yellow a in Diabetic Nephropathy: A Meta-Analysis of Randomized Controlled Trials - Fu, Shunlian; Zhou, Qian; Gao, Yang; Yang, Yunjiao; Chen, Huizhen; Yuan, Lijun; Li, Zinan; Chen, Qiu (Frontiers in Pharmacology, 2022)
Background: Diabetic kidney disease (DKD) is a chronic progressive disorder which is a leading cause of chronic kidney disease (CKD). As an important pathogenesis of DKD, the overproduction of reactive oxygen species (ROS) and the inflammatory response have been considered central mediators in the progression of DKD. Herbal products are increasingly being applied as antioxidants and anti-inflammatory agents. Of those, the effect of hydroxyl safflower yellow A (HSYA) on oxidative stress and inflammatory reactions has gradually been investigated for DKD treatment, which may provide therapies for DKD with new insights and promote its application in clinical practice. Methods: We searched CNKI, the Chinese Biomedical Literature Database, the Wanfang Database, PubMed, and Embase from the establishment date of the database to 22 April 2022. The included literature in our study was randomized controlled trials (RCTs) using HSYA to treat DKD. We performed a meta-analysis by calculating the standard mean difference (SMD) with a 95% confidence interval (CI). The inverse-variance method with a random effect was used in our meta-analysis using Stata software and RevMan software. Results: A total of 31 articles with 31 groups containing a total of 2487 participants were included in this meta-analysis. The pooled results showed a statistical improvement in the following measurements: fasting blood glucose (FBG), postprandial blood glucose (PBG), blood urea nitrogen (BUN), urinary albumin excretion rates (UAER), serum creatinine (SCR), hypersensitive C-reactive protein (hsCRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), fasting insulin (FINS), total cholesterol (TC), triglycerides (TGs), hemoglobin A1c (HbA1C), homeostasis model assessment insulin resistance (HOMA-IR), and malondialdehyde (MDA). Conclusion: HSYA can effectively treat DKD by inhibiting inflammatory reactions and oxidative stress, decreasing blood glucose and blood lipids, and improving renal function indices. However, more RCTs are still needed in the future to further demonstrate the effect of HSYA on biomarkers of oxidative stress and inflammatory reactions in patients with DKD due to the low quality and small sample size of the literature included in this study. Systematic Review Registration: PROSPERO: CRD 42021235689